Семантико-словотвірна характеристика композитних інноваційних іменників у романі «Правда і кривда» М. Стельмаха - Бабій, Ірина; Babiy, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2013)
Стаття присвячена розгляду іменникових індивідуально-авторських новотворів у романі «Правда і кривда» М. Стельмаха. Проаналізовано семантику та структуру складних лексичних інновацій. Виявлено оцінно- експресивне забарвлення авторських неологізмів у романі.In the article the author’s individual noun innovations and their functions in M. Stelmakh novel «Pravda i Kryvda» (The Truth and Abuse) are studied. Semantic and of complex lexical innovations is analyzed. In the article it is confirmed that individual author’s neologisms enrich the expressive means of a language. They are characterised by semantic and stylistic flexibility and are important descriptive and expressive means in fictional text. The largest group among the complex author’s neologisms which can be found in the novel «Pravda i Kryvda» (The Truth and Abuse) are the names of people. In the article a word forming analysis of compositive innovations of nouns is mad and peculiarities of itґs functioning are revealed. The evaluative and expressive colouring of complex lexical innovations in the novel «Pravda i Kryvda» is underlined.
Semantic and Word Forming Characteristics of noun Compositive Innovations in the Novel «Pravda i Kryvda»
Keywords: новотвір; авторський неологізм; лексичні інновації; неолексема; складне слово; композит; юкстапозит; neologism; author’s neologism; lexical innovations; neo-lexeme; complex word; composite; jukstaposite